2020
DOI: 10.1021/jacs.0c05050
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Single Atoms Coupling with Oxygen Vacancies Boosts Oxygen Evolution Reaction in Acid Media

Abstract: Simultaneous realization of improved activity, enhanced stability, and reduced cost remains a desirable yet challenging goal in the search of electrocatalysis oxygen evolution reaction (OER) in acid. Herein, we report a novel strategy to prepare iridium single-atoms (Ir-SAs) on ultrathin NiCo2O4 porous nanosheets (Ir–NiCo2O4 NSs) by the co-electrodeposition method. The surface-exposed Ir-SAs couplings with oxygen vacancies (VO) exhibit boosting the catalysts OER activity and stability in acid media. They displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
301
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(304 citation statements)
references
References 45 publications
3
301
0
Order By: Relevance
“…As such, the traditional OER model was investigated using a standard three-electrode system. [34][35][36][37] Co(OH) 2 and Co(OH) x -Ag electrodes were tested for comparison (Figures S27 and S28, Supporting Information). Figure 5a exhibits the linear sweep voltammetry (LSV) curves with iR compensation of all samples.…”
Section: Kinetics Characterization Of Surface Catalytic Reactionmentioning
confidence: 99%
“…As such, the traditional OER model was investigated using a standard three-electrode system. [34][35][36][37] Co(OH) 2 and Co(OH) x -Ag electrodes were tested for comparison (Figures S27 and S28, Supporting Information). Figure 5a exhibits the linear sweep voltammetry (LSV) curves with iR compensation of all samples.…”
Section: Kinetics Characterization Of Surface Catalytic Reactionmentioning
confidence: 99%
“…Therefore, the Pt-site could play a protecting role for stabilizing the Ni valence state and a distributary role by binding OH and H species to low the deactivation of absorption sites in case of over-binding of intermediates on the active sites for NiO/Ni heterostructure coupled single-atom Pt. 53 Based on the above finding, we further explore the reaction barrier of the fabricated catalysts for H2O splitting in alkaline conditions, consisting of the dissociation of H2O molecule of Volmer step and the subsequent conversion of H to H2, which mainly depends on how OH and H bond to the active sites on the surface of the catalysts. 54 We found that both H and OH bind weakly to the pure NiO surface.…”
Section: Synthesis and Characterization Of Ptsa-nio/ni Catalyst The mentioning
confidence: 94%
“…One solution to this conundrum is to develop suitable catalysts with high efficiency and low overpotential [27]. However, most of the excellent OER catalysts with high activity and durability are not stable in acidic solutions [28]. They are easily oxidized and decomposed in a strong acid system, which is one of the indispensable working conditions for PEMWE [29].…”
Section: H O L → O + 4h + 4ementioning
confidence: 99%
“…In order to maximize the utilization of each active site (approaching 100%) as well as shed light on the effect of the structure of active centers and ligating atoms on the OER activity, catalysts have thus been continuously downsized to the single-atom (SA) level. Single-atom catalysts (SACs) have emerged as a hot new branch of heterogeneous catalysts due to their excellent catalytic performance and financial benefits [28]. Owing to the high requirements for the dispersion, activity, and stability of the atoms, an appropriate support must be selected to optimize the physiochemical properties of the metal atoms anchored [81].…”
Section: Coordination Environmentmentioning
confidence: 99%
See 1 more Smart Citation